2002
DOI: 10.1074/jbc.m111145200
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand-inducible Epidermal Growth Factor Receptor/Anaplastic Lymphoma Kinase Chimera Promotes Mitogenesis and Transforming Properties in 3T3 Cells

Abstract: receptor (EGFR). Upon transfection in NIH 3T3fibroblasts, the EGFR/ALK chimera was correctly synthesized and transported to the cell surface, where it was fully functional in forming high versus low affinity EGF-binding sites and transducing an EGF-dependent signal intracellularly. Overexpression of the EGFR/ALK chimera in NIH 3T3 was sufficient to induce the malignant phenotype; the appearance of the transformed phenotype was, however, conditionally dependent on the administration of EGF. Moreover, the EGFR/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
2
25
0
1
Order By: Relevance
“…A recent paper using an EGF-activated EGFR-ALK chimera suggests that the MAPK cascade is only very weakly induced in response to an activation of the ALK tyrosine kinase (29). This may be due to the fact that this chimeric receptor is not fully activated in response to EGF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper using an EGF-activated EGFR-ALK chimera suggests that the MAPK cascade is only very weakly induced in response to an activation of the ALK tyrosine kinase (29). This may be due to the fact that this chimeric receptor is not fully activated in response to EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Lysates or immunocomplexes were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), transferred onto nitrocellulose filters, and immunoblotted according to previously described procedures. [26][27] Bound proteins were visualized with…”
Section: Cell Lysis and Protein Analysismentioning
confidence: 99%
“…We have previously shown that in this chimera the biochemical and biologic properties of ALK are controlled by EGF stimulation, thus making it possible to dissect ALK enzymatic function under condition of controlled ligand-induced activation. 26 Therefore, fibroblastic NIH-3T3 cells expressing the chimera EGFR/ALK (NIH-EGFR/ALK) were cultured at 37°C for different time periods in the absence or presence of EGF prior to lysis and subsequent in vitro DGK assay on total homogenate. As shown in Figure 2, an increase in total DGK activity was observed after EGF treatment, further supporting a direct correlation between ALK activation and stimulation of a cellular DGK enzymatic function.…”
Section: Coupling Of Alk With Dg Kinase Activitymentioning
confidence: 99%
See 2 more Smart Citations